Career Coupling: Career Making in the Elite World of Musicians and Scientists - Wagner, Izabela (Qualitative Sociology Review, 2022)
This article analyzes the interaction between the careers of people working in artistic and intellectual worlds. Two ethnographic studies constitute the basis for the analysis of career building in connection with the careers of other actors. The concept of career coupling represents the process by which professional success is achieved through the forging of relationships between novice and elite actors. Career coupling in the social world of virtuoso musicians is compared to that of career coupling in the social world of elite scientists. It was found that both groups achieve status in a similar fashion by moving through a three-stage process: (1) matching; (2) active collaboration; and, (3) passive collaboration. It is argued that the analysis of career coupling developed here can also be transferred to other professional fields.